PENGARUH KEBIJAKAN TARIF IMPOR BERAS TERHADAP VOLUME IMPOR BERAS INDONESIA DARI THAILAND - I Gusti Agung Ngurah Gede, Satria Utama; Anak Agung Bagus Putu Widanta (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to analyze the impact of rice import tariff policies on the volume of Indonesia's rice imports from Thailand during the period 1993–2022. In addition to rice import tariff policies, this research also considers factors such as Indonesia's rice production, the population of Indonesia, the Rupiah to USD exchange rate, and international rice prices. The multiple linear regression analysis method is used to examine the relationship between these variables and the volume of Indonesia's rice imports from Thailand. The results indicate that rice import tariff policies have a significant effect on the volume of Indonesia's rice imports from Thailand, due to the increase in import rice prices in line with the applicable policies. The findings also show that Indonesia's rice production has a negative and significant effect on the volume of rice imports from Thailand, suggesting that fluctuations in domestic rice production influence the volume of imports. Indonesia's population has a positive and significant impact, as the growing population leads to increased rice consumption, which ultimately affects rice imports. The Rupiah to USD exchange rate also has a negative and significant influence, indicating that both depreciation and appreciation of the Rupiah strongly affect rice import demand. The price of Thai rice has a negative and significant effect on Indonesia's rice imports from Thailand. This research provides recommendations to the government, relevant institutions, and the public as consumers in addressing the future stability of rice in Indonesia.